(untitled) (Southwestern Research Journal, 2023)
Ayurveda is an ancient science which deals with the Ayu (Life) of all human beings. Kayachikitsa is one of the most important branch/speciality among primary eight branches of Ayurveda. In Ayurveda, Kayachikitsa is such a unique branch which deals with ‘Kaya’ meaning ‘Sharira (body)/Mana (mind)/Antaragni (Digestive fire)’ and ‘Chikitsa’ meaning ‘treatment’. It deals with diseases suffering entire body and mind so, it is correlated to Internal Medicine in modern medicine. It is described as the superior branch of Astanga Ayurveda and it is given prime importance due to its wide field of application in diagnosis and treatment of various diseases affecting human beings. Kayachikitsa is a very important and leading speciality in Ayurveda. So, considering this fact, we summarize about Kayachikitsa speciality and its importance in this article.